Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Di Sekolah Smk 3 Pskd Jakarta Utara - Muhammad Ulil Albab; Akhmad Fauzi Hamzah (Journal of Innovative and Creativity, 2025)
This study examines the principal's strategies in fostering teacher professionalism at SMK 3 PSKD North Jakarta, using a qualitative method and a case study approach. Data were collected through interviews, observations, and documentation, with data analysis conducted using triangulation methods. The aim of this research is to identify the principal's role in building teacher professionalism at SMK 3 PSKD North Jakarta. Additionally, this study seeks to understand how the principal's strategies influence the quality of teaching and the effectiveness of learning in the school. The findings indicate that the principal plays a vital role as the highest leader in the school, serving as a good role model for both teachers and students, and acting as a nurturing figure akin to a parent, using both direct and indirect approaches. The strategies employed to enhance teacher professionalism include: (1) discipline, which is key to achieving success and excellence; (2) deliberation, where the principal holds monthly meetings to evaluate the teaching and learning activities; and (3) reward-giving, where the principal provides recognition as a form of appreciation for teachers who perform well.